Introduction to topo-philosophy - Krzanowski, Roman (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
In philosophy, it is always refreshing to introduce unconventional ideas. It requires a certain audacity from the author; he or she may face the wall of silence or be shunned by academia, both treatments being undesirable. However, these are more rewarding than gathering laurels for beating the dead philosophical cats like Humes, Leibnitzs, Wittgensteins, Whiteheads, and others, a practice that for many philosophers is their life's opus. Bartłomiej Skowron’s book Part and Whole: Towards Topo-Ontology, published by Oficyna Wydawnicza Politechniki Warszawskiej in 2021, certainly does not fall into this category. Skowron undertakes a discovery trip into an unknown land in his book, exploring new philosophical territories.